Aparências da forma e forma do espaço: análise da configuração espacial de residências unifamiliares dos anos 1970 em João Pessoa PB - Aldrigue, Maryá de Sousa (2012)
Assuming that the form of a building shell and its content the spatial form are distinct dimensions of architecture - however indivisible and interdependent -, this study focus, in the light of the Social Logic of Space (HILLIER; HANSON, 1984), on the intrinsic properties through which domestic space was structured in a sample of single-family dwellings built in João Pessoa (PB) during the 1970s - when the vocabulary of modern architecture still prevailed in Brazil though sharing the urban scene with other architectural trends -, in order to investigate regularities or divergences underlying their conception. These dwellings were originally classified (ARAÚJO, 2010a) in five categories defined according to the form of their building shells and to their prevailing construction techniques: (1) Brazilian modern legacy (considered as truly Brazilian modern style); (2) Paulista architecture (that refers to the modern production of São Paulo, Brazil, from the 1950s through the 1970s); (3) experiences of rationalization and prefabrication ; (4) experiences of adaptation to the climate (referring to a design strongly influenced by the hot and humid climate of North-eastern Brazil); and (5) hybrid (to account for a kind of stylistic hybridism that includes formal attributes, which evoke our colonial past). This study aims to determine, through the analyses of nineteen cases that represent each category, whether this taxonomy corresponds to distinct modes of spatial configuration. This research therefore proposes an approach to the classification of domestic architecture based on topological properties. The dwellings spatial organization was represented, quantified and analyzed, their spatial properties explored in consonance with one another and with the literature. Results pointed out that there is no evidence of a reciprocal relationship between the formal look of the built shells and their respective spatial structures